Annual performance of the second-generation variable-geometry oscillating surge wave energy converter. (November 2021) - Kelly, Michael; Tom, Nathan; Yu, Yi-Hsiang; Wright, Alan; Lawson, Michael
Abstract: Recent studies in wave energy have highlighted the need for a structured innovation approach in wave energy converter (WEC) design because cost-of-energy estimates have remained high. One such innovation being investigated by the National Renewable Energy Laboratory is WEC geometry control, which uses control surfaces in combination with an oscillating surge WEC (OSWEC) to increase device availability and power generation while limiting structural costs. This study performs the first analysis of annual performance for a novel OSWEC with geometry control to understand how the geometry control affects availability, annual power generation, and structural loadings like the power-take-off (PTO) torque or surge foundation force. Device hydrodynamic coefficients are calculated using linear potential theory for six geometry configurations. A nonideal PTO system is assumed and quadratic viscous damping losses are considered. Annual performance is evaluated and compared for three U.S. wave energy sites. The WEC geometry and PTO system are controlled on a sea-state basis to optimize for power capture while remaining under limits set on motion amplitude and structural loads. Results indicate that geometry control can increase availability up to 25 days in an average year depending on design limits, increase average power generation, and significantly reduce peak structural loads. Highlights: First analysis of the effects of geometry control on annual performance. Annual performance irregular wave analysis includes viscous and nonideal PTO losses. Performance compared for different control strategies, locations, and load limits. Geometry control increases availability by up to 25 days in an average year. Geometry control increases average annual power production by up to 7.5%.